Study in vitro and in vivo of anti-diabetic and anti-obesity active principles of curcubita ficifolia Bouche and Vaccinium angustifolium ait - Sánchez Villavicencio, Mayra Luz (Universidad Autónoma Metropolitana, 2017)
Anti-diabetic and anti-obesity properties of C. ficifolia Bouche and V. angustifolium Aiton have been reported in in vivo and in vitro assays and thus are relatively well studied. However, their mechanisms of action and/or active principles still remain unclear. The inhibitory effect of Fermented Blueberry Extract (FBE) on triglyceride (TG) accumulation in adipocytes was attributed to fractions FBE (F1), phenolics (F2) and chlorogenic acid (F3-2) (70%) at a dose of 5 µg/ml. Further fractionation and purification yielded other pure compound, Catechol (CAT) that inhibited adipogenesis by 75%. In vivo FBE had a tendency to reduce glycaemia in DIO mice but did not have any effect on body weight with a significant difference on concentration 7.6 ml/kg of FBE respect to control DIO and CHOW. In Intraperitoneal glucose tolerance test only significant differences were observed between treatments from NBE extract and control DIO from the first 15 and 60 min. Examination of intracellular signalling components (p-Akt, p-AMPK) and transcriptional factors (SREBP-1c and PPAR?) was carried out by Western blot analysis. Treatment with NBE, F1, F3-2, CAT and CA decreased p-AKT, whereas p-AMPK tended to increase with F1, F2 and F3-2. The expression of SREBP1-c was not significantly modulated. In contrast, PPAR? decreased in all experimental groups inhibiting adipogenesis. These results demonstrated that FBE contains compounds with anti-adipogenic activity, which can serve to standardize nutraceutical preparations from fermented blueberry juice and to develop novel compounds with anti-obesity properties Fermentation conferred novel and potent in vitro anti-diabetic and anti-obesity properties to blueberry extract. Fermented blueberry extract (FBE) may represent a complementary therapy and a source of novel therapeutic agents against type 2 diabetes mellitus. In addition, this is one of the first steps in the identification of the principles responsables of its anti-diabetic and anti-obesity effects. The optimal concentration of C. ficifolia crude extract (20 µg/mL) was tested in C2C12 murine myoblasts for glucose transport assay since skeletal muscle is an important insulin-target tissue in glucose homeostasis. However, it did not induce glucose transport when compared to control. C. ficifolia crude extract was also tested at the optimal concentration (20µg/ml ) on adipogenesis process using 3T3- L1 cells, showing 70% of inhibition in the intracellular content of triglycerides (TG). Preliminary results from C. ficifolia extract and primary fractions showed effect in F16 and F17 with significance in respect to control DMSO. For the activity of glucose 6-phosphatase, H4IIE hepatocytes treated with 40 µg/ml of extract displayed approximately 60% enzyme inhibition. The primary fractionation of C. ficifolia crude extract also represents an advance for the development on the phytochemistry from the plant that might allow us to identify the active components responsible for its potential anti-diabetic and anti-obesity for the development of new therapeutic agents for the treatment of type 2 diabetes and obesity.; Las propiedades antidiabéticas y antiobesidad de V. angustifolium y C. ficifolia han sido reportadas in vivo e in vitro, por lo que ambas plantas ya cuentan con antecedentes importantes en la investigación de la diabetes y la obesidad. Sin embargo, sus mecanismos de acción y/o principios activos aún no están claros. Los tratamientos con el extracto fermentado FBE (F1), Fenoles (F2) y ácido clorogénico (CA) (F3-2) de V. angustifolium (Fermented Blueberry Extract) mostraron inhibición significativa en la acumulación de triglicéridos de hasta 70- 75% en concentraciones de 5 µg/ml. El fraccionamiento y purificación permitió la obtención de otro compuesto puro, el catecol (CAT), que inhibió la adipogénesis hasta en un 75%. Ambos compuestos mostraron un papel importante en la disminución de trigliceridos. En los tratamientos que se llevaron a cabo in vivo, FBE mostró reducción significativa en la glucemia de ratones “Diet-induced models of obesity” DIO con respecto al control DIO y Chow. Sin embargo, no tuvo ningún efecto sobre el peso corporal. En la prueba de tolerancia a la glucosa intraperitoneal sólo se observaron diferencias significativas entre los tratamientos del extracto no fermentado con el control DIO en los primeros 15 y 60 min. Por analisis de Western Blot, también se investigó el papel de p-Akt, p-AMPK, SREBP1c y PPAR gamma en células 3T3-L1 tratadas con NBE, FBE, 7 fracciones y cuatro compuestos puros de V. Angustifolium. Con NBE, F1, F3-2, CAT y CA se observó un decremento para p-AKT, así como una tendencia para incrementar pAMPK, especialmente en los tratamientos de F1, F2 y F3-2. Para la expresión de SREBP1-c no se observó ningun cambio significativo. En contraste, PPAR? mostró un decremento significativo en todos los grupos experimentales que mostraron efecto inhibitorio en la acumulación de trigliceridos. Estos resultados demuestran que el extracto fermentado de blueberry contiene compuestos con actividad antiadipogénica, la cual podria servir para la estandarización de preparaciones nutracéuticas, asi como para el desarrollo de nuevos compuestos con propiedades antiobesidad. Para C. ficifolia se observó un efecto inhibitorio en una concentración de 20µg/ml sobre el contenido de triglicéridos con el extracto completo de hasta un 70% con respecto al control. En el analisis de Western Blot, las celulas 3T3-L1 tratadas con el extracto de C. ficifolia y fracciones primarias presentando una disminución en el proceso de adipogénesis. Se analizaron tambien las vias de señalización de p-AMPK, donde se observó tendencia a incrementar la forma fosforilada de AMPK en las celulas tratadas con el extracto de C. ficifolia con respecto al control DMSO; sin embargo, no hubo diferencias significativas en la activación de AMPK. C. ficifolia no presentó actividad positiva en el transporte de glucosa en comparación con el control en concentración óptima de 20µg/ml. Para la actividad enzimatica de glucosa-6- fosfatasa se observó inhibición de la enzima en celulas H4IIE de hepatocitos tratados con 40 µg/ml del extracto de C. ficifolia. La fermentación de V. angustifolium presentó propiedades antidiabéticas y antiobesidad novedosas y potentes in vitro. Esto confirma lo observado en investigaciones anteriores, por lo que estos resultados confieren un paso más en la investigación referente a los posibles mecanismos de acción y las vias de señalización por las cuales estos compuestos ejercen su acción. El fraccionamiento primario de C. ficifolia tambien representa un adelanto para el desarrollo de nuevos agentes terapéuticos para el tratamiento de la diabetes mellitus tipo 2, además de contribuir en la investigación relacionada a la identificación de componentes responsables de sus efectos antidiabético y de antiobesidad.